The art of ceremony voices of renewal from indigenous Oregon - Dobkins, Rebecca J. (The Jacob Lawrence series on American artists, 2022)
"The practice of ceremony offers ways to build relationships between the land and its beings, reflecting change while drawing upon deep relationships going back millennia. Ceremony may involve intricate and spectacular regalia but may also involve simple tools, such as a plastic bucket for harvesting huckleberries or a river rock that holds heat for sweat. The Art of Ceremony provides a contemporary and historical overview of the nine federally recognized tribes in Oregon, through rich conversations with tribal representatives who convey their commitments to ceremonial practices and the inseparable need to renew language, art, ecological systems, kinship relations, and political and legal sovereignty. Vivid photographs illuminate the ties between land and people at the heart of such practice, and each chapter features specific ceremonies chosen by tribal co-collaborators, such as the Siletz Nee Dosh (Feather Dance), the huckleberry gathering of the Cow Creek Umpqua, and the Klamath Return of C'waam (sucker fish) Ceremony. Part of a larger global story of Indigenous rights and cultural resurgence in the twenty-first century, The Art of Ceremony celebrates the power of Indigenous renewal, sustainable connection to the land, and the ethics of responsibility and reciprocity between the earth and all its inhabitants"--